2019
DOI: 10.1590/1413-785220192702214897
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Body Composition in Elderly Runners: Six-Year Follow-Up

Abstract: Objective: To evaluate bone mineral density (BMD) and body composition over a six-year period in elderly long-distance runners. Methods: We analyzed the medical records of elderly athletes who were long-distance runners, were participants of the IOT-HCFMUSP Orthogeriatric Group, and had their BMD evaluated between 2001 and 2007; of these athletes, 11 were included in the study. Inclusion criteria: athletes should be long-distance runners, should not stop long-distance running during the six-year period, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A more developed and trained musculature, individuals with higher lean mass have a more active lifestyle, with more appropriate diet patterns. 3 The study by Scott et al 21 showed that the higher muscle density of the leg decreases postural oscillations, suggesting that the increased risk of fractures in sarcopenic obesity can be explained by the low quality of the muscle, which can lead to worsening of postural balance. Regarding anthropometric variables, the higher the height, the higher the speed of balance in the sit-to-stand test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more developed and trained musculature, individuals with higher lean mass have a more active lifestyle, with more appropriate diet patterns. 3 The study by Scott et al 21 showed that the higher muscle density of the leg decreases postural oscillations, suggesting that the increased risk of fractures in sarcopenic obesity can be explained by the low quality of the muscle, which can lead to worsening of postural balance. Regarding anthropometric variables, the higher the height, the higher the speed of balance in the sit-to-stand test.…”
Section: Discussionmentioning
confidence: 99%
“…They are characterized by the gradual loss of bone mass and the weakening of bones, making them more fragile and susceptible to fractures 1 due to decreased levels of hormones that act in the process of bone remodeling, mechanical load imposed on the skeleton, inadequate feeding, calcium absorption and vitamin D. Studies show an association between lower BMD with lower BMI in young 2 and older men. 3 Falls are prevalent in older adults; however, in those with osteoporosis and osteopenia, falls can be more disastrous, being related to hip fracture. One in 15 older adults die in the hospital phase, and 30.35% die in one year due to complications resulting from these falls, and fractures.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, the high scores of non-aquatic athletes due to terrestrial exercises appear to result in a greater effect on BMD and BMC. Despite the positive effect of exercise on BMD, it is difficult to correlate between BMD and athlete performance (Alonso et al, 2019). Among the athletes, the higher body weight seems to suggest a higher BMD (Byun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%